The Distinction of Government Administration and Judicial Institutions in The Umayyad Dynasty - Meirison, Meirison; Saharuddin, Desmadi (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2021)
This paper aimed to reveal the government administration system's distinction in finance and justice that existed in the Umayyad. The Umayyad had the right side in improving government administration, finance, economy, and justice. To what extent was the reform and distinction of government administration, finance, and judiciary pursued by the Umayyad that led to society's benefit besides the atrocities he had ever made? The researchers conducted a library study with a descriptive analysis approach, collected sources, verified, and interpreted the policies and updates made by the Umayyad. The study showed the Umayyad had made distinctions and reforms that brought about a lot of benefits. Although they seemed the duplication of Persian and Roman governments, financial administration policies still referred to Islamic rules and were not influenced by Rome and Persia. The most significant reform was establishing the Mazalim Court separated from the ordinary judiciary. The perpetrators of this crime were not ordinary people but state officials handled directly by the caliph and judges who could act reasonably and act decisively. A vast area of neat administration supported the economic activity, and along with Islamic law, the Umayyad did not exercise a monopoly. However, this government lasted shortly for 90 years (661-750 AD) because of the power succession policy, the ruler's lifestyle, fanaticism, and political opponents' attack.